Reorientation of Digital Platform-Based Business Models: Dynamic Analysis Capabilities and Ambidextrous Strategy for Transforming Indonesian State-Owned Enterprises into a Digital Ecosystem - Vika Fransisca (Al-Makki Publisher, 2025)
Digital transformation has pushed Indonesian State-Owned Enterprises (SOEs) to reorient their business models toward digital platforms to address technological disruption and increasingly complex market dynamics. However, this change requires not only technology adoption but also strengthened organizational capabilities and adaptive strategies. This study aims to analyze how SOEs build and integrate dynamic capabilities ( sensing, seizing, transforming ) and implementing ambidextrous strategy in an effort to reorient business models towards a digital ecosystem. The study used a qualitative case study approach with five strategic state-owned enterprises as the objects, involving in-depth interviews, internal document studies, and observations of digital strategy implementation. The results show that sensing and seizing capabilities are fundamental in responding to digital opportunities, but the transformation phase faces significant challenges related to bureaucratic structures and organizational culture. Furthermore, an ambidextrous strategy proved crucial in maintaining a balance between exploring digital innovation and exploiting core competencies. State-owned enterprises that are able to implement this strategy in a structured manner demonstrated higher success in building an inclusive, adaptive, and sustainable platform ecosystem. This study provides a conceptual contribution to the public sector digital transformation literature and offers practical guidance for stakeholders in managing the business transition towards a digital ecosystem-based model.